The modern directions of clustering tourism industry: digital convergence - A. A. Vartumyan; N. N. Novoselova; V. V. Khubulova; T. N. Lavrova (Современная наука и инновации)
In the globalizing space, tourism is a process or phenomenon that affects the level of well-being of various contingents, states and peoples. At the present stage of socio-economic development, the transformation of the formed cluster model in the tourism industry is necessary. Global trends and trends dictate the transition to new development realities that involve the transition from innovative systems to digital systems. In this context, it is necessary to develop and implement conceptually new models of management of tourist systems both at the federal level and at the local level. The key goal of stimulating tourism with digital technologies is to promote digital and physical convergence and achieve the goals of intellectual tourism through the creation of digital platforms.